Quantitative Perfusionsbildgebung in der Magnetresonanztomographie = Quantitative perfusion imaging in magnetic resonance imaging - Zöllner, Frank G.; Uhrig, Tanja; Zimmer, Fabian; Meyer, Melissa; Riffel, Philipp; Hausmann, Daniel; Schönberg, Stefan; Weis, Meike (Der Radiologe, 2016)
Clinical/methodical issue: Magnetic resonance imaging (MRI) is recognized for its superior tissue contrast while being non-invasive and free of ionizing radiation. Due to the development of new scanner hardware and fast imaging techniques during the last decades, access to tissue and organ functions became possible. One of these functional imaging techniques is perfusion imaging with which tissue perfusion and capillary permeability can be determined from dynamic imaging data. Standard radiological methods: Perfusion imaging by MRI can be performed by two approaches, arterial spin labeling (ASL) and dynamic contrast-enhanced (DCE) MRI. While the first method uses magnetically labelled water protons in arterial blood as an endogenous tracer, the latter involves the injection of a contrast agent, usually gadolinium (Gd), as a tracer for calculating hemodynamic parameters. Performance: Studies have demonstrated the potential of perfusion MRI for diagnostics and also for therapy monitoring. Achievements: The utilization and application of perfusion MRI are still restricted to specialized centers, such as university hospitals. A broad application of the technique has not yet been implemented. Practical recommendations: The MRI perfusion technique is a valuable tool that might come broadly available after implementation of standards on European and international levels. Such efforts are being promoted by the respective professional bodies.
Gesehen am 11.02.2019